2014
DOI: 10.19070/2377-8075-140003
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of Chitosan-H, Resveratrol, β-Carotene and Propolis and their Chitosan Hydrogels on Balb/C Mouse 3T3 Fibroblast Cells

Abstract: Chitosan [10] which is produced commercially by de-acetylation of chitin is a natural polysaccharide composed of randomly distributed β-1, 4-linked D-glucosamine and N-acetyl α-glucosamine.Chitosan is non-toxic, biocompatible, bio-degradable and has muco-adhesive properties and as a result became widely used in the pharmaceutical field as a carrier system for drugs, hormones, proteins, enzymes and genes [11][12][13][14]. Chitosan is positively charged in acid medium because the amino groups become protonated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…We determined the survival rates at a growth medium concentration of 1mg/ml which is reported to be in line with other research and which may be considered as on the upper recommended level [16] of concentration. The three cell lines tested consisted of a standard cell line bought from the National Repository for Biological Materials and two self-established human tooth pulp fibroblast cell lines (H1 cell line and H2 cell line) from two different people.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We determined the survival rates at a growth medium concentration of 1mg/ml which is reported to be in line with other research and which may be considered as on the upper recommended level [16] of concentration. The three cell lines tested consisted of a standard cell line bought from the National Repository for Biological Materials and two self-established human tooth pulp fibroblast cell lines (H1 cell line and H2 cell line) from two different people.…”
Section: Discussionsupporting
confidence: 56%
“…A Balb/c 3T3 mouse fibroblast cell line (The National Repository for Biological Materials, Sandringam) was maintained and cultured under standard conditions [13]. The two human dental pulp fibroblast cultures were established as previously described [14][15][16]. Briefly freshly extracted impacted 3 rd molars were collected in Dubecco's Modified Eagels Medium, the middle third of the pulp cultured and the cells between the 3 rd and 5 th passage used.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies [23] on cytotoxicity we found that the presence of chitosan with various substances, like anti-oxidants (resveratrol, propolis and β-carotene) and others (naproxen, ibuprofen) increased the cell survival rate of mouse 3T3 fibroblast cells significantly in comparison to the mentioned substances alone.…”
Section: Cytotoxicitymentioning
confidence: 89%
“…The cytotoxicity was examined as previously reported [23]. Briefly, the cells were first grown to near confluency, diluted to a final cell suspension containing approximately 3×10 5 cells/ml and plated out insets of 96 well plates.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…A chemical bonding capacity through the interaction between some functional monomers and the calcium of residual hydroxyapatite may contribute favorably to the bonding effectiveness [26][27][28][29] but, fluoride affects the enamel surface rendering it more resistant to demineralization. Fluoride in low concentrations favors the formation of fluoro-hydroxyapatite, which is less susceptible to acidic solubility than hydroxyapatite [34,35]. Therefore, it is recommended to use these preventive agents after bonding the brackets when self-etch adhesive systems are used.…”
Section: Discussionmentioning
confidence: 99%